Příspěvek k debatě o etice historické práce Plagiarism Defence Strategies. Contribution to the Debate on the Ethics of Historiographic Research - Crhák, Ondřej; Konečný, Tomáš (Dějiny – teorie – kritika, 2022)
The presented paper is a reaction to the panel discussion on ethics in historiography, organized at the 12th Congress of Czech Historians in September 2022 under the chairmanship of Professor Milan Hlavačka. The main purpose of this discussion was to review recent plagiarism affairs in Czech historical science. In our text, we tried to describe and analyse some of related defence strategies and evaluate the risk of such behaviours. The main goal of this study is to break down the defences against unethical behaviour in general. We consider this paper a start of a serious discussion on this topic within Czech academia.